Boosting ultrafast and durable sodium storage of hard carbon electrode with graphite nanoribbons. (15th October 2022) - Zhong, Weihao; Cheng, Dejian; Zhang, Minglu; Zuo, Huajiang; Miao, Lei; Li, Zhenghui; Qiu, Guojian; Cheng, Ao; Zhang, Haiyan
Abstract: Hard carbons are emerged as one of the most promising candidates for sodium storage, but suffer from poor rate performance and inferior cycling stability. Herein, we design novel hierarchically hollow hard carbon spheres by combining hydrothermal growth and catalytic graphitization. The carbon spheres have a unique tremella-like morphology assembled from ultrathin heterostructured nanosheets with interwoven graphitic ribbons/amorphous carbon textures. When employed as anode in sodium-ion batteries, the 3D hierarchical structure is able to minimize the reaction length and accelerate the ion transfer; meanwhile, the graphite nanoribbons can offer electron immigration pathways and serve as supporting framework to protect the electrode off crack. As such, the carbon electrode delivers a high capacity of 278 mAh g −1 at 0.1 A g −1, and presents no dramatic capacity loss during a long-term charge/discharge test for 1000 cycles. More importantly, the hard carbon electrode has unexpectedly ultrafast sodium storage capability. Even under a very high current density of 10 A g −1, it retains a large capacity of 146 mAh g −1, giving a retention rate of 68% against the capacity at 0.05 A g −1, which is rarely achieved for state-of-the-art hard carbon anodes. Graphical abstract: Image 1